HUBUNGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS POWERPOINT TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS V PADA MATA PELAJARAN IPAS DI SDN MERJOSARI 3 KOTA MALANG - Helena Margareta; Firsta Bagus Sugiharto; Chusnul Chotimah (Jurnal Lensa Pendas, 2025)
The aim of this research is to examine the relationship between interactive learning media and student learning outcomes. This research used quantitative research (Quantitative Research) which is a product moment correlation, namely a type of research that uses variable X data and Variable Y data. Variable X represents the use of interactive learning media and variable Y reflects student learning outcomes. Used this method, researchers can measure the extent of relationship between these two variables and understand their impact on student learning outcomes in more detail. The results obtained from this research indicate that the use of interactive learning media based on Power Point has been proven to have a significant impact on student learning outcomes at SDN Merjosari 3, Malang City. Before using interactive media, student learning outcomes were very low with a percentage of only 53.35% of the average value, which means the achievement standard was 75%. However, after implementing interactive learning media, there was a significant increase in student learning outcomes, with a percentage reaching 89% of the average score, which means above the achievement standard, namely 75%. Therefore, it can be concluded that the effective use of interactive learning media can improve student learning outcomes at SDN Merjosari 3, Malang City.